2009
DOI: 10.1021/la902902k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Salt Crystal Whiskers on Porous Nanoparticle Coatings

Abstract: Salt crystal whiskers were grown from aqueous solution on porous nanoparticle silica coatings. Coated substrates were partially immersed in an aqueous potassium chloride solution and then kept in a controlled relative humidity chamber for whisker growth. The salt solution was pulled into the porous coating, reaching a steady level about 1 h after immersion. Crystals with whisker morphologies, typically 2-50 microm in lateral dimension and up to approximately 1 cm in length, emerged from the coating surface at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…The saturated salt solution forms a thin film along walls [15] and sallows solution transport to the crust depending on humidity and the solution concentration [15,38]. Therefore, the solution film along the cylindrical wall sustains the crust migration.…”
Section: Salt Crust Migration Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…The saturated salt solution forms a thin film along walls [15] and sallows solution transport to the crust depending on humidity and the solution concentration [15,38]. Therefore, the solution film along the cylindrical wall sustains the crust migration.…”
Section: Salt Crust Migration Mechanismmentioning
confidence: 99%
“…The effect of the substrate hydrophobicity or hydrophilicity on the topological character of precipitates has been observed in other salts such as K 2 Cr 2 O 7 [34], ammonium chloride [13], potassium nitrate, potassium chloride, and ammonium chloride [13,38]. …”
Section: Effects Of Substrate Surface Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, we discuss the underlying physics of the growth of NaCl nanowires on the GO membrane. It has been reported that the growth of ionic nanowires is determined by solution diffusion and evaporation. Figure a,b shows the typical morphologies of a nanowire base. The nanowire has a pyramid base and a layer of dendritic crystals, both covered by GO sheets.…”
Section: Resultsmentioning
confidence: 99%
“…We utilized the technique of Zhang et al [24,25] for the growth of KCl whiskers, which in turn relies on the previous observations of Gyulai [26] and Shichiri [27]. In this technique, glass slides are cleaned in an ultrasonic bath containing detergent water, then rinsed in ethanol and distilled water, and dried at 120 o C for 1 hour.…”
Section: Whisker Growthmentioning
confidence: 99%